The serial books „School of mathematics“ and terminology of Lithuanian mathematics - Pekarskas, Vidmantas; Pekarskienė, Aldona (Lietuvos matematikos rinkinys, 2003)
Lithuanian mathematical terms used by authors and translators of serial „School of mathematics" in 1971–1988 are reviewed in this article.